Trends and Variability of Rice, Maize, and Wheat Yields in South Asian Countries: A Challenge for Food Security - Poudel, Mahadeb Prasad; Chen , Shwu-En (Asian Journal of Agriculture and Rural Development, 2012)
During the last six decades, the yield and production of rice, maize, and wheat grew remarkably in South Asian region. As these cereals are staple foods, the growth and fluctuation of yields greatly impacts on food security. This study aims to examine the growth patterns and variability of rice, wheat, and maize yields in South Asian countries namely Bangladesh, India, Nepal, Pakistan, and Sri Lanka. Utilizing the yield data during 1961-2010, we applied the linear and quadratic regressions for yield trends and variability analyses. Quadratic model was fitted well in all data sets except wheat yield in Pakistan. A clear indication of slowing growth rates was observed for wheat yield in Bangladesh and India, as well as a significant increase in maize yield variability was realized in Bangladesh, India, Pakistan, and Sri Lank. The factors influencing for slowing yield growth rates are considered as comparative disadvantage of wheat to Boro rice in case of Bangladesh, whereas depletion of soil nutrient contents in the rice-wheat production areas and negative impact of climate change in India. The slowing yield growths exerted a challenge for food security in Bangladesh and India. Thus, policy implementations are urgent to improve the wheat yield growth and maize yield stabilization in the concerning countries.